Factors affecting the exports of natural rubber in Malaysia / Siti Khadijah Mohamad (Faculty of Business and Management, 2007)
The rubber industry plays an important role in the Malaysian economic. The exportation of natural rubber may be influenced by several factors such as the price of natural rubber, rubber-planted area and the consumption of synthetic rubber. Year by year, the price of natural rubber is increasing. The cost of producing the natural rubber is quite high due to the high pay of labor. It is feared that the increase in the price of natural rubber in Malaysia may lead to the lower demand from other countries towards the natural rubber in Malaysia. There is uncertainty of future exportation of natural rubber due to the unstable price of natural rubber as well as the existence and consumption of synthetic rubber This study is conducted by using the secondary data. All of the data required are obtained from various sources such as the internet, magazines, books and past research in order to understand the export performance of natural rubber in Malaysia. There are five types of analysis in SPSS program that has been used in the study to analyze the data including T-test, correlation of coefficient, Pearson's correlation, ANOVA test and Model Summary. This study is done in order to explain the effect of the factors towards the export performance of natural rubber.